FINEMAP: efficient variable selection using summary data from genome-wide association studies - Benner, Christian; Spencer, Chris C.A.; Havulinna, Aki S.; Salomaa, Veikko; Ripatti, Samuli; Pirinen, Matti (Bioinformatics, 2016)
Motivation: The goal of fine-mapping in genomic regions associated with complex diseases and traits is to identify causal variants that point to molecular mechanisms behind the associations. Recent fine-mapping methods using summary data from genome-wide association studies rely on exhaustive search through all possible causal configurations, which is computationally expensive. Results: We introduce FINEMAP, a software package to efficiently explore a set of the most important causal configurations of the region via a shotgun stochastic search algorithm. We show that FINEMAP produces accurate results in a fraction of processing time of existing approaches and is therefore a promising tool for analyzing growing amounts of data produced in genome-wide association studies and emerging sequencing projects. Availability and implementation: FINEMAP v1.0 is freely available for Mac OS X and Linux at http://www.christianbenner.com. Contact: christian.benner@helsinki.fi or matti.pirinen@helsinki.fi